Infectious Complications after Thermal Ablation of Liver Tumors - Jiang Lin, Xie Xiaoyan, Xu Ming (Advanced Ultrasound in Diagnosis and Therapy, 2025)
Infectious complications are common postoperative issues after thermal ablation of liver tumors, including liver abscess, biliary tract infection, sepsis, which can significantly impact patient prognosis. Common pathogens associated with these infections include Escherichia coli, Enterococcus, Klebsiella pneumoniae, Staphylococcus aureus. Diagnosing infectious complications after ablation requires an integrated approach, combining clinical manifestations, laboratory tests, and imaging examinations. Notably, specific imaging findings may help identify liver abscess, biliary tract infection and infection secondary to gastrointestinal perforation. Risk factors for post-ablation infection include a history of biliary interventions or dysfunction of the sphincter of Oddi, prior arterial chemoembolization or transarterial radioembolization, and ablation performed at anatomically challenging sites. For high-risk patients, appropriate preventive measures should be implemented. Treatment typically involves antibiotics and catheter drainage, with commonly used antibiotics including penicillins, cephalosporins, quinolones, metronidazole. Understanding the diagnosis, risk factors, prevention, and treatment strategies for post-ablation infections is critical for optimizing patient outcomes. This review aims to summarize the current literature on infections after thermal ablation of liver tumors, detailing the common infection sites, pathogens, diagnostic approaches, prevention strategies, and treatment methods. Additionally, it explores the potential mechanisms underlying infection development after ablation.